Surveillance of ICU Patients for Candida auris in a Suburban Chicago Hospital System: Results of a Limited Trial. (October 2020) - Lavin, Mary Alice; Schora, Donna; Fisher, Adrienne; Kufner, Bridget; Lim, Rachel; Monsalud, Cherie Faith; Shah, Mona; Zelencik, Shane; Singh, Kamaljit
Abstract : Background: Candida auris prevalence in Illinois, particularly in the metropolitan Chicago area, is high. The Illinois Department of Public Health recommends empiric contact precautions for patients with a tracheostomy or requiring mechanical ventilation from skilled nursing facilities (vSNFs) or long-term acute-care hospitals (LTACHs) who are admitted to an acute-care hospital. Cases of C. auris infection and colonization are reportable to the Illinois Extensively Drug Resistant Organism Registry (XDRO Registry). NorthShore University HealthSystem (NSUHS) actively screens adult intensive care unit (ICU) admissions from LTACHs and vSNFs for CA. Methods: NSUHS is a 4-hospital system located north of Chicago with 750 beds, 4 ICUs and ∼64, 000 annual admissions. Beginning in April 2019, a composite axilla–groin swab was collected from all ICU LTACH or vSNF admissions. Composite swabs are cultured on Inhibitory Mold Agar. In July 2019, an ICU clinical case of C. auris was identified from a ventilated patient admitted from an outside hospital prompting the expansion of screening to include acute-care hospital transfers. To evaluate the value of screening criteria, a medical record review and retrospective query of the XDRO Registry was performed for all screened patients. Because cocolonization with carbapenemase-producing organisms (CPO) has been reported, CPO status was also queried. Results: Between April 1 and October 31, 2019, 70 patients were screened. Two screened patients did not meet the screening criteria (Fig. 1). No patients, with the exception of the clinical case, were found to be colonized with CA. The XDRO Registry query identified no patients with C. auris . Of the 70 patients, 9 (13%) had a CPO. Of those screened, 14 (20%) had a tracheostomy and/or mechanical ventilation (Table 1). Conclusions: Querying the XDRO registry at admission in combination with a medical record review appears adequate to identify patients admitted to a NSUHS ICU with C. auris and CPOs. Targeting patients admitted with a tracheostomy and/or mechanical ventilation may further reduce the number of screening cultures performed. Funding: None Disclosures: None